2021
DOI: 10.1186/s12885-020-07666-8
|View full text |Cite
|
Sign up to set email alerts
|

CA724 predicts overall survival in locally advanced gastric cancer patients with neoadjuvant chemotherapy

Abstract: Background Serum tumor markers including AFU, AFP, CEA, CA199, CA125 and CA724, are of great importance in the diagnosis, prognostic prediction and recurrence monitoring of gastrointestinal malignancies. However, their significance in gastric cancer (GC) patients with neoadjuvant therapy (NCT) is still uncertain. The aim of this study was to evaluate the predictive value of these six tumor markers in locally advanced GC patients who underwent NCT and curative surgery. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…CA724 is a relatively common type of nonspecific tumor marker, which has extremely high sensitivity for non-small cell lung cancer and gastric cancer, and its sensitivity for diagnosing gastric cancer is about 60% [ 21 , 22 ]. AFP is a commonly used tumor serum marker, and its level is low in healthy adult serum, but its level is increased in hepatocellular carcinoma [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…CA724 is a relatively common type of nonspecific tumor marker, which has extremely high sensitivity for non-small cell lung cancer and gastric cancer, and its sensitivity for diagnosing gastric cancer is about 60% [ 21 , 22 ]. AFP is a commonly used tumor serum marker, and its level is low in healthy adult serum, but its level is increased in hepatocellular carcinoma [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients with a high CONUT had shorter PFS and OS than those with low CONUT, especially in patients with high CA724 value. Tong Y and others also found that CA724 was an independent factor for prognosis and could be used to TNM stage in locally advanced gastric cancer patients who received neoadjuvant chemotherapy and curative resection (Tong et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, heavy metals may contribute to the MSI status and HER2 gene expression, but the pathogenic mechanism needs to be further studied. Besides that, the level of serum tumor biomarkers plays an important role in the progression of GC [ 55 ]. A previous study indicated that CA72-4 was correlated with the TNM stage in GC patients [ 56 ].…”
Section: Discussionmentioning
confidence: 99%